3DNSTi / Nb-O composite material based on template agent P123 as well as preparation method and application of 3DNSTi / Nb-O composite material
The 3DNSTi/Nb-O composite material constructed through Nb doping and template agent P123 solves the problems of slow kinetics and poor cycle stability of magnesium-based hydrogen storage materials, and achieves efficient hydrogen storage performance and long-life hydrogen storage capacity, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202510669543.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-08-15
AI Technical Summary
The existing magnesium-based hydrogen storage materials have problems such as high working temperature, slow kinetics and poor cycle stability. This is mainly because hydrogen atoms need to overcome the high energy barrier, catalyst charge recombination, and nanoparticle agglomeration, and structural collapse and high reversible hydrogen storage capacity are difficult to maintain.
Vacancy defects are constructed through transition metal element doping, combined with template agent to assist in synthesis of specific morphology, and a one-step hydrothermal method is used to prepare a three-dimensional structure composed of anatase-type TiO2 nanosheets to form an Nb-doped 3DNSTi/Nb-O composite material to improve electron transfer efficiency and structural stability.
The long life, high capacity and rapid rate of MgH2 hydrogen storage material were achieved, the hydrogen release temperature was reduced to 190℃, and the hydrogen release amount reached 6.4 wt.% within 5 minutes at 300℃. After 1500 cycles, the hydrogen storage capacity remained at 7.1 wt.%, which was suitable for large-scale production.
Smart Images

Figure CN120483246A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen storage materials, and particularly relates to a 3DNSTi / Nb-O composite material based on a template P123, and a preparation method and application thereof. Background Art
[0002] Magnesium-based hydrogen storage materials are characterized by abundant reserves, low prices, and high hydrogen storage capacity. However, they have problems such as high operating temperature, slow kinetics, and poor cycle stability. The reasons for this are mainly concentrated in the following three aspects:
[0003] 1. Magnesium lacks d-orbital electrons that interact with hydrogen antibonding orbitals, which makes it difficult for H2 molecules to dissociate on the Mg surface;
[0004] 2. During the hydrogenation process, H first forms MgH2 with a dense crystal structure with the Mg surface layer. The diffusion coefficient of H in the MgH2 layer is low, which hinders the diffusion of H into the Mg body, resulting in a slowdown in the overall rate.
[0005] 3. During the hydrogen absorption and desorption cycle, MgH2 will experience particle coarsening and active site masking, resulting in a decrease in the cyclic hydrogen capacity.
[0006] The main solution at present is to improve it through nano-scaling and adding catalysts.
[0007] Among them, the basic principle of the technical solution based on nano-scale is to significantly regulate the thermodynamic and kinetic behavior of magnesium-based hydrogen storage materials through quantum size effects and surface effects. When the material particle size is reduced to the nanoscale, the synergistic improvement of specific surface area and porosity shortens the hydrogen diffusion path to the submicron level, significantly improving the hydrogen migration rate and significantly improving the hydrogen absorption and desorption kinetics of nano-magnesium-based materials. In addition, when the material size is reduced to the nanoscale, the significant increase in interfacial energy can induce lattice distortion, increase instability, and achieve optimization of thermodynamic properties. For example, existing literature 1, ("Hydrogenstorage capabilities enhancement of MgH2 nanocrystals" Int J Hydrogen Energy, 2024, 85: 269-273), prepared MgH2 nanocrystals by high-energy mechanical spheroidal graphite process, which increased the surface energy of the material and promoted the breaking of Mg-H bonds, accelerating the diffusion of H atoms. The technical effect of releasing 5.1wt% H2 within 75 minutes at 340°C was achieved. At the same time, the dehydrogenation activation energy was reduced from 136.0kJ / mol H2 of commercial MgH2 to 126.69kJ / mol H2, and the dehydrogenation temperature was only 174°C. However, such nano-based technical solutions all have high surface energy characteristics that lead to particle agglomeration, which in turn leads to the annihilation of reactive active sites and structural collapse during the cycle, ultimately leading to capacity decay rate. In addition, the production processes that achieve nano-scaling, such as high-energy ball milling or vapor deposition, all have the problem of high production costs.
[0008] The technical solution based on catalyst does not have the above-mentioned technical problems of nano-scaling, because its basic principle is:
[0009] 1. Introducing a catalyst as an intermediate in MH electron transfer to accelerate electron transfer and reduce the H dissociation energy barrier;
[0010] 2. The catalyst is dispersed on the surface of MgH2, which inhibits the grain coarsening during the cycle and avoids the easy agglomeration defect of nano-MgH2;
[0011] 3. The interface between the catalyst and the Mg matrix provides abundant hydride nucleation sites and hydrogen diffusion pathways, helping H to penetrate into the interior through the formed MgH2 layer.
[0012] Among them, transition metal Ti and its compounds are typical heterogeneous hydrogen storage catalysts. Ti has a strong affinity for hydrogen, and its incompletely filled d orbitals easily interact with the σ* bond orbitals of H during dissociation, which is conducive to the dissociation of H2 molecules and further reduces the H dissociation barrier. In addition, Ti has multiple valence states (Ti 0 、Ti 2+ 、Ti 3+and Ti 4+ ), and its multivalent compounds as active intermediates can promote electron transfer between Mg-H through the transition between valence states, thereby promoting H dissociation.
[0013] Titanium dioxide TiO2 has been shown to be an effective catalyst for improving the hydrogen storage performance of MgH2 because of its large reserves, low cost, easy preparation and stable chemical properties. For example, existing document 2, ("Catalytic mechanism of TiO2quantum dots on the de / re-hydrogenation characteristics of magnesium hydride" Int J Hydrogen Energy, 2021, 46: 37340-37350) synthesized TiO2 with a particle size of 2.5-4.0nm as a catalyst to improve the hydrogen storage performance of MgH2, achieving the initial desorption temperature of MgH2 from 360 ° C to 260 ° C, Mg-TiO2: QDs sample absorbed 6.10wt.% of hydrogen in only 77 seconds at 280 ° C, but, when the number of cycles reached 80 times, the hydrogen storage capacity was significantly reduced, leaving only 6.0wt.%. This technical solution shows that by introducing TiO2 as a catalyst, the hydrogen absorption and desorption kinetics can be effectively improved, but the technical solution still has the problem of poor cyclic stability. The reason is,
[0014] 1. TiO2 is prone to electron-hole recombination under thermal conditions, which reduces the electron transfer efficiency and leads to a decrease in long-term cycle stability;
[0015] 2. The multivalent nature of Ti can weaken the Mg-H bond through interfacial electron transfer, thereby leading to passivation and structural collapse of the catalytic active sites.
[0016] The problem of low electron mobility can be solved by constructing vacancy defects and surface adsorbed anions or cations. For example, existing literature 3 (《Enhancing the cycling stability of MgH2 using nitrogen modified titanate》J Mater Chem A, 2023, 11(22):11748-11754) uses N-doped modified K2Ti6O 13, reducing its band gap. When used as a catalyst, it can reduce the initial dehydrogenation temperature of MgH2 to 195°C. After 200 cycles at 300°C, the capacity is 6.8wt.%, and the capacity retention rate is increased to 94.4%. However, the technical problem with this technology is that it requires the preparation of a reducing KNH2 precursor in a water- and oxygen-proof environment, and then a reduction reaction with TiO2 to introduce nitrogen into the TiO2 lattice. Therefore, there are problems with high production conditions, which lead to a significant increase in energy consumption and preparation costs.
[0017] To address the passivation and structural collapse issues of the above-mentioned catalytic active sites, the interface state between TiO2 and the MgH2 matrix and the dispersion uniformity can be improved by constructing a special micromorphology. The catalyst with a special structure can be fully broken and evenly dispersed during the ball milling process, fully contacting with MgH2, increasing the active sites and hydrogen diffusion pathways. For example, existing document 4 ("Oxygen Vacancy-Rich 2D TiO2 Nanosheets: ABridge Toward High Stability and Rapid Hydrogen Storage Kinetics of Nano-Confined MgH2" Nanomicro Lett, 2022, 14(1):144) uses a multi-step reaction to prepare graphite-like sheet-like 2D TiO2 as a catalyst. After 100 cycles at 300°C, the capacity retention rate can reach 98.5%. An organic titanium source is used as a titanium source for a solvothermal reaction, and multi-level regulation is used to form two-dimensional TiO2 with graphite-like flakes. MgH2 nanoparticles are then in situ grown on the 2D TiO2 to construct a MgH2 / TiO2 heterostructure. This technical solution improves the cyclic stability of MgH2 by constructing a special morphology, but its hydrogen storage capacity is only 2.7wt.%, and the synthesis technology route is complex and requires precise control, making it difficult to achieve industrial-scale preparation.
[0018] According to existing technologies, the problems that need to be solved are mainly concentrated in the following three aspects:
[0019] 1. Hydrogen atoms need to overcome a high energy barrier to diffuse in the bulk phase. At the same time, the surface hydrogen dissociation / recombination reaction during the cycle is limited by the catalyst charge recombination, which reduces the electron transfer efficiency. This results in a decrease in hydrogen release rate and capacity after the cycle, making it difficult to meet practical needs. Element doping can be used to change the catalyst band gap, hinder charge recombination, and maintain electron transfer efficiency.
[0020] 2. During long-term hydrogen absorption and desorption cycles, irreversible structural collapse caused by nanoparticle agglomeration, grain boundary migration, and interfacial stress accumulation results in loss of active sites and blockage of hydrogen diffusion channels. High reversible hydrogen storage capacity is difficult to maintain cyclic stability. By constructing a catalyst with a special morphology, the structural degradation of MgH2 during the cycle is constrained.
[0021] 3. The existing synthesis process of long-lasting composite materials is lengthy, energy-intensive, and has low safety and operability. It is necessary to develop a simple, low-energy preparation process. Summary of the Invention
[0022] The purpose of this invention is to provide a 3DNSTi / Nb-O composite material based on the template P123, as well as its preparation method and application, to address the problems in the prior art. On the one hand, the invention creates vacancy defects through transition metal doping to improve electron transfer efficiency; on the other hand, the addition of a template aids in the synthesis to create a special morphology to maintain structural stability. At the same time, no water or oxygen isolation is required, and a one-step hydrothermal method is used to overcome the low operability technical problems of partial reduction and step-by-step multi-stage reactions. The basic principles involved are as follows:
[0023] 1. By doping with transition metal elements, the energy band structure of TiO2 can be changed, the band gap can be reduced, and vacancy defects can be introduced, thereby improving the electron transfer efficiency between the catalyst and MgH2 and hindering charge-hole recombination during the catalytic process, thereby reducing the Mg-H dissociation energy barrier and improving the electron transfer stability;
[0024] 2. By constructing materials with specific morphologies, the problems of passivation and structural collapse of active sites in conventional TiO2 during the reaction are resolved, thereby improving the dispersion of TiO2 on the MgH2 matrix. This ultimately achieves the technical effects of increasing reactive active sites, connecting H diffusion pathways, and promoting H dissociation. Furthermore, the material forms an encapsulation structure with MgH2, maintaining structural stability during the cycle.
[0025] In terms of preparation technology, based on the existing hydrothermal synthesis technology, the technical effect is achieved through the following three technical features:
[0026] 1. Dissolve the niobium source and titanium source in the solvent, i.e. Nb 5+ With Ti 4+ Coexisting in the reaction solution, through the hydrothermal method, the titanium source is hydrolyzed to generate TiO2 while in-situ doping Nb, so that Nb atoms are doped into the TiO2 lattice;
[0027] 2. The micromorphology is adjusted by introducing a fluoride ion regulator. The specific principle is that fluoride ions have strong electronegativity and are easily adsorbed on Ti atoms. Based on the above characteristics, the introduction of a fluoride ion regulator induces the formation of nanosheets, thus achieving the effect of adjusting the micromorphology;
[0028] Specifically, in the present invention, ammonium fluorotitanate not only acts as a titanium source and hydrolyzes to generate TiO2, but also has the function of synchronously releasing fluoride ions. At the same time, combined with the introduction of boric acid as a fluoride ion-eliminating agent, the micromorphology can be controlled.
[0029] 3. Using P123 as a template, TiO2 nanosheets can be self-assembled to form a 3D structure.
[0030] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:
[0031] A 3DNSTi / Nb-O composite material based on a template agent P123 is prepared, wherein niobium oxalate is used as a niobium source, ammonium fluorotitanate is used as a titanium source and a fluoride ion regulator, boric acid is used as a fluoride ion regulator, and P123 is used as a template agent. The 3DNSTi / Nb-O composite material based on the template agent P123 is first synthesized by a hydrothermal method, and then heat-treated in air to remove P123 to obtain 3DNSTi / Nb-O. The 3DNSTi / Nb-O is anatase-type TiO2, and Nb elements are doped into the TiO2 lattice. The 3DNSTi / Nb-O has oxygen vacancies. The microstructure of the 3DNSTi / Nb-O is a three-dimensional structure composed of nanosheets. The specific surface area is 25-35 m 2 / g.
[0032] A preparation method of a 3DNSTi / Nb-O composite material based on a template agent P123 comprises the following steps: first, preparing a niobium source, a fluoride ion regulator, a titanium source, and a template agent in a certain proportion as raw materials; then, under certain conditions, placing the niobium source, the fluoride ion regulator, the titanium source, and the template agent in deionized water and stirring and dissolving them to obtain a reaction solution; then, subjecting the reaction solution to a hydrothermal reaction; after the reaction is complete, filtering, washing, and drying the resulting precipitate to obtain a Nb-doped TiO2 nanosheet self-assembled 3D structure composite material; finally, under certain conditions, subjecting the Nb-doped TiO2 nanosheet self-assembled 3D structure composite material to a heat treatment to remove the template agent, thereby finally obtaining a template agent-based 3DNSTi / Nb-O composite material having a self-assembled 3D structure, referred to as 3DNSTi / Nb-O;
[0033] The niobium source is niobium oxalate; the titanium source is ammonium fluorotitanate; the fluoride ion regulator is boric acid, and ammonium fluorotitanate is also a fluoride ion regulator; the template is P123;
[0034] The mass ratio of niobium oxalate, boric acid and ammonium fluorotitanate is (0.025-0.3):(0.25-2):1, and the mass ratio of template to titanium source is 1:(1-4);
[0035] The stirring and dissolving conditions are as follows: the stirring and dissolving temperature is 25-60°C and the stirring and dissolving time is 10-60 minutes;
[0036] The reaction temperature is 110-200°C and the reaction time is 4-10h;
[0037] The drying conditions are as follows: drying temperature is 60-80°C and drying time is 6-12h;
[0038] The heat treatment temperature is 500-950° C., the heating rate is 2-5° C. / min, and the heat treatment time is 1-8 hours.
[0039] A method for preparing a magnesium hydride composite hydrogen storage material based on 3DNSTi / Nb-O comprises the following steps: under certain conditions, ball-milling MgH2 and 3DNSTi / Nb-O to prepare a magnesium hydride composite hydrogen storage material based on 3DNSTi / Nb-O, referred to as MH-3DNSTi / Nb-O;
[0040] The ball milling conditions are as follows: the ball milling hydrogen pressure is 2-10 bar, the ball-to-powder ratio is (20-40):1, and the ball milling speed is 200-500 rpm.
[0041] The initial dehydrogenation temperature of the obtained MH-3DNSTi / Nb-O is 185-230°C; when the dehydrogenation temperature is 300°C and the dehydrogenation time is 5 minutes, the dehydrogenation amount is 6.0-6.5wt.%; when the number of hydrogen absorption and dehydrogenation times is 1000-1500 times, the hydrogen storage capacity has no obvious change, and the dehydrogenation capacity is maintained at 6.9-7.1wt.%; and the complete dehydrogenation time is less than 15 minutes.
[0042] The beneficial technical effects of the material obtained by the present invention can be seen from the following tests:
[0043] XRD detection of the present invention shows that the 3DNSTi / Nb-O composite material prepared based on the template P123 is anatase TiO2, and no organic diffraction peak appears, indicating that the template P123 has been completely removed. In addition, combined with subsequent tests, it is known that the diffraction peak corresponding to the (101) crystal plane of anatase TiO2 shifts with the increase of the amount of Nb added. Calculation using the Scherrer formula shows that the grain size decreases with the increase of the amount of Nb added. The test results show that heat treatment can completely remove the template P123, and the addition of the template has no substantial effect on the material phase structure. In addition, the Nb element is successfully doped into the TiO2 lattice, causing lattice distortion, thereby improving the electron transfer efficiency.
[0044] The EPR test of the present invention shows that the 3DNSTi / Nb-O composite material prepared based on the template agent P123 shows obvious oxygen vacancy signals. Combined with the XRD test results, it can be seen that the Nb element is successfully doped into the TiO2 lattice, causing the conversion between the chemical valence states of Ti / Nb, triggering electron transfer and calmly generating O V This phenomenon shows that the introduction of Nb elements can not only promote the electron transfer between Mg-H and improve the hydrogen dissociation efficiency, but also increase the reaction active sites and hydrogen diffusion pathways through OV;
[0045] SEM testing of the present invention shows that the 3DNSTi / Nb-O composite material prepared based on the template agent P123 exhibits a three-dimensional structure composed of nanosheets, and there is no collapse phenomenon after high-temperature heat treatment. This structure is easily dispersed with MgH2, which can significantly increase the active sites and hydrogen diffusion pathways.
[0046] The BET test of the present invention shows that the specific surface area of the 3DNSTi / Nb-O composite material prepared based on the template P123 is 31.5m 2 / g, an increase of 69.4% compared with the one without additives;
[0047] Hydrogen storage performance testing of the present invention shows that: the initial hydrogen desorption temperature of the magnesium hydride composite hydrogen storage material based on 3DNSTi / Nb-O is reduced to 190°C, the hydrogen desorption amount reaches 6.4wt.% within 5 minutes at 300°C, and the hydrogen desorption amount reaches 6.7wt.% within 25 minutes; the material is activated after hydrogen absorption and desorption cycles at a hydrogen absorption pressure of 0.8MPa and a hydrogen desorption pressure of 0.004MPa at 300°C, and the hydrogen desorption capacity increases to 7.1wt.%; and after 1500 hydrogen absorption and desorption cycles, the capacity does not decay at all and is stably maintained at 7.1wt.%.
[0048] Therefore, the present invention has the following advantages over the prior art:
[0049] 1. The present invention provides a preparation method of 3DNSTi / AO composite materials based on template-assisted synthesis. Through the synergistic effect of A doping and nanosheet self-assembly to construct a 3D structure, the coexistence of multivalent Ti / A and abundant oxygen vacancies are introduced, and a consumption-regeneration balance is achieved. This improves the efficiency of electron transport and atomic diffusion, provides abundant reaction active sites, and effectively improves the catalytic activity and stability of the prepared material.
[0050] 2. The material prepared by the present invention is further used to catalyze the performance of MgH2 hydrogen storage, achieving long life, high capacity and fast rate of MgH2 hydrogen storage material, achieving more than 1500 hydrogen absorption and desorption cycles without capacity decay and maintaining a reversible hydrogen storage capacity of 7.1wt.%. After 1500 hydrogen absorption and desorption cycles, the MgH2 hydrogen storage material can still completely dehydrogenate within 15 minutes, maintaining fast kinetics.
[0051] 3. The preparation method of the present invention has simple process and low cost, can utilize existing production equipment, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 XRD patterns of 3DNSTi / Nb-O prepared in Example 1 and Comparative Example 1;
[0053] Figure 2 : This is the oxygen vacancy EPR pattern of 3DNSTi / Nb-O prepared in Example 1;
[0054] Figure 3 SEM images of 3DNSTi / Nb-O prepared in Example 1 and Comparative Example 1;
[0055] Figure 4 3DNSTi / Nb-O prepared in Example 1 and Comparative Example 1:
[0056] Figure 5 This is a comparison chart of the dehydrogenation of the composite hydrogen storage materials prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 in ascending order of temperature increase;
[0057] Figure 6 1 is a comparison chart of the isothermal hydrogen release rates of the composite hydrogen storage materials prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4;
[0058] Figure 7 Graph showing the cycle performance of the composite hydrogen storage materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0059] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0060] Example 1
[0061] A preparation method of a 3DNSTi / Nb-O composite material based on a template agent P123 specifically comprises the following steps: first, preparing raw materials with a molar ratio of niobium oxalate, boric acid and ammonium fluorotitanate of 0.15:0.5:1 and a mass ratio of P123 to ammonium fluorotitanate of 1:3; then, under the conditions of a stirring and dissolving temperature of 50°C and a stirring and dissolving time of 30 minutes, placing ammonium fluorotitanate, niobium oxalate, boric acid and P123 in 70 mL of deionized water for stirring and dissolving to obtain a reaction solution; then, under the conditions of a hydrothermal temperature of 130°C and a hydrothermal time of 6 hours, subjecting the reaction solution to a hydrothermal reaction; and after the reaction is completed, , filtering the obtained precipitate, washing and drying to obtain a Nb-doped TiO2 nanosheet self-assembled 3D structure composite material, finally, heat-treating the Nb-doped TiO2 nanosheet self-assembled 3D structure composite material at a heating rate of 3°C / min, a heat treatment temperature of 750°C, and a heat treatment time of 2h to remove the template P123, and finally obtaining a 3DNSTi / Nb-O composite material based on the template P123 having a self-assembled 3D structure, referred to as 3DNSTi / Nb-O, and the Ti / Nb-O obtained in specific Example 1 is referred to as 3DNSTi / Nb-O-2;
[0062] The washing is completed under the condition that the clear liquid is neutral; the drying conditions are that the drying temperature is 80°C and the drying time is 12 hours;
[0063] In order to prove the phase structure of the obtained 3DNSTi / Nb-O-2, XRD test was carried out. The test results are as follows Figure 1 As shown, 3DNSTi / Nb-O-2 does not have the characteristic peaks of organic matter P123, but does have the characteristic peaks of anatase TiO2. In addition, combined with subsequent tests, it can be seen that the diffraction peak corresponding to the (101) crystal plane of anatase TiO2 shifts with the increase of Nb addition. Calculations using the Scherrer formula show that the grain size decreases with the increase of Nb addition. The test results show that the template P123 can be completely removed through the heat treatment in step 1, and the Nb element is successfully doped into the TiO2 lattice, causing lattice distortion and thus improving the electron transfer efficiency.
[0064] In order to further prove the electronic structure characteristics of the obtained 3DNSTi / Nb-O-2, oxygen vacancy EPR test was carried out. The test results are as follows Figure 2 As shown, 3DNSTi / Nb-O-2 has obvious O V Combined with the XRD test results, it can be seen that the Nb element is successfully doped into the TiO2 lattice, causing the conversion between the Ti / Nb chemical valence states, triggering electron transfer and calmly generating O VThis phenomenon shows that the introduction of Nb element can not only promote the electron transfer between Mg-H and improve the dissociation efficiency of hydrogen, but also V Increase reaction active sites and hydrogen diffusion pathways.
[0065] In order to verify the microstructure of the obtained 3DNSTi / Nb-O-2, SEM test was carried out. The test results are shown in the figure below. Figure 3 As shown, the microstructure of 3DNSTi / Nb-O-2 is a three-dimensional structure composed of nanosheets, and there is no collapse phenomenon after high-temperature heat treatment.
[0066] In order to prove the pore characteristics of the obtained 3DNSTi / Nb-O-2, BET specific surface area test was carried out. The test results are as follows Figure 4 As shown, the specific surface area of 3DNSTi / AO-2 is 31.5m 2 / g.
[0067] In order to demonstrate the role of the obtained 3DNSTi / Nb-O-2 as a magnesium hydride hydrogen storage catalyst, a magnesium hydride composite hydrogen storage material based on 3DNSTi / Nb-O-2 was prepared and the hydrogen storage performance was tested.
[0068] The preparation method of the magnesium hydride composite hydrogen storage material based on 3DNSTi / Nb-O is as follows: MgH2 and 3DNSTi / Nb-O are ball-milled and mixed under the conditions of a ball-milling hydrogen pressure of 10 bar, a ball-to-powder ratio of 35:1, and a ball-milling speed of 400 rpm to prepare a magnesium hydride composite hydrogen storage material based on 3DNSTi / Nb-O, referred to as MH-3DNSTi / Nb-O. The MH-3DNSTi / Nb-O obtained in specific Example 1 is referred to as MH-3DNSTi / Nb-O-2.
[0069] In order to prove the initial hydrogen desorption temperature of the obtained MH-3DNSTi / Nb-O-2, a temperature programmed desorption TPD test was performed. The test results are as follows Figure 5 As shown, the initial dehydrogenation temperature of the MH-3DNSTi / Nb-O-2 composite hydrogen storage material is 190°C.
[0070] In order to demonstrate the hydrogen desorption kinetics performance of the obtained MH-3DNSTi / Nb-O-2, a hydrogen desorption kinetics test was performed.
[0071] Among them, the hydrogen absorption / desorption performance test, that is, the cycle performance test, consists of a hydrogen desorption kinetics test and a hydrogen absorption kinetics test. The specific conditions of the hydrogen desorption kinetics test, referred to as the hydrogen desorption test, are as follows: a hydrogen desorption temperature of 300°C, a hydrogen desorption pressure of 0.004 MPa, and a hydrogen desorption time of 25 minutes;
[0072] The specific conditions of the hydrogen absorption kinetics test, referred to as the hydrogen absorption test, are as follows: hydrogen absorption temperature of 300°C, hydrogen absorption pressure of 0.8 MPa, and hydrogen absorption time of 25 min;
[0073] The specific method of the cycle performance test, referred to as the cycle test, is to perform a hydrogen release test and a hydrogen absorption test in sequence to complete one cycle test.
[0074] The hydrogen release test results are as follows: Figure 6 As shown in the figure, when the hydrogen desorption time is 5 minutes, the amount of hydrogen desorbed is 6.4 wt.%; when the hydrogen desorption time is 25 minutes, the amount of hydrogen desorbed is 6.7 wt.%. The test results show that MH-3DNSTi / Nb-O-2 has good hydrogen absorption and desorption kinetics.
[0075] In order to prove the cyclic performance test of MH-3DNSTi / Nb-O-2, the cyclic test results are shown in Figure 2. Figure 6 As shown,
[0076] In the first cycle, the hydrogen storage capacity of MH-3DNSTi / Nb-O-2 was 6.7 wt.%;
[0077] At 170 cycles, the hydrogen storage capacity of MH-3DNSTi / Nb-O-2 reached 7.1 wt.%, which is higher than the hydrogen storage capacity of the first cycle. This is because hydrogen atoms preferentially penetrate through the surface during the initial cycle. As the number of cycles increases, hydrogen gradually penetrates into the bulk of the material, activating internal hydrogen storage sites and gradually increasing the capacity, thus achieving activation.
[0078] After 1500 cycles, the hydrogen storage capacity of MH-3DNSTi / Nb-O-2 was 7.1wt.%. Compared with the cycle performance after 170 cycles, there was no substantial change in the hydrogen storage capacity, indicating that MH-3DNSTi / Nb-O-2 has excellent hydrogen absorption and desorption cycle stability.
[0079] Based on the test results of Example 1, the following conclusions can be drawn: when P123 is added as a template, growth can be induced, self-assembly can be achieved, and a three-dimensional structure constructed by nanosheets can be formed. At the same time, oxygen vacancies can be achieved. P123 can be completely removed by subsequent heat treatment, and a BET specific surface area of 31.5 m 2 / g, ultimately achieving a significant improvement in the reversible hydrogen storage capacity, long-cycle stability and rapid hydrogen absorption and desorption performance of MgH2.
[0080] In order to demonstrate the role of P123 as a template in the technical solution, comparative examples 1, 2 and 3 are provided, wherein:
[0081] Comparative Example 1 is a composite material prepared without adding P123, which serves as a basic reference;
[0082] Comparative Example 2 and Comparative Example 3 are composite materials prepared by adding common templates, polyetherimide PEI and polydimethylsiloxane PDMS, respectively, to further demonstrate the role of P123 as a template in the technical solution.
[0083] Comparative Example 1
[0084] A method for preparing a NSTi / Nb-O composite material without adding a template, wherein the steps not specifically described are the same as those in Example 1, except that no P123 is added. The obtained Ti / AO composite material is referred to as NSTi / Nb-O. Furthermore, the subsequently obtained magnesium hydride composite hydrogen storage material is referred to as MH-NSTi / Nb-O.
[0085] The XRD test results of NSTi / Nb-O are as follows: Figure 1 As shown, there is no substantial difference from the 3DNSTi / Nb-O obtained in Example 1. The test results show that adding P123 as a template has no substantial effect on the phase structure.
[0086] The SEM test results of NSTi / Nb-O are as follows Figure 3 As shown in Figure 2, the microstructure of NSTi / Nb-O obtained without adding P123 is a randomly dispersed nanosheet structure. Compared with the 3DNSTi / Nb-O obtained in Example 1, it can be seen that the addition of P123 can cause the nanosheet structure to self-assemble into a three-dimensional structure.
[0087] The BET test results of NSTi / Nb-O are as follows: Figure 4 As shown in the figure, the specific surface area of NSTi / Nb-O obtained without adding P123 is 18.6m 2 Compared with the 3DNSTi / Nb-O obtained in Example 1, it can be seen that the addition of P123 can significantly increase the specific surface area by 69.4%.
[0088] Combining the results of XRD, SEM and BET tests, it can be seen that the addition of P123 does not affect the physical structure, but can significantly change the micromorphology, causing the material to self-assemble into a 3D structure, thereby significantly increasing the specific surface area.
[0089] The TPD test results of MH-NSTi / Nb-O are as follows: Figure 5 As shown in FIG, the initial dehydrogenation temperature of the MH-NSTi / Nb-O composite hydrogen storage material is 196° C. Compared with the 3DNSTi / Nb-O obtained in Example 1, it can be seen that the introduction of P123 as a template can further reduce the initial dehydrogenation temperature.
[0090] The hydrogen release test results of MH-NSTi / Nb-O are as follows: Figure 6As shown in the figure, the amount of hydrogen released is 5.7 wt.% when the dehydrogenation time is 5 minutes, and 6.6 wt.% when the dehydrogenation time is 25 minutes. Compared with the 3DNSTi / Nb-O obtained in Example 1, it can be seen that the introduction of P123 as a template has no substantial effect on the total amount of hydrogen released, but it can significantly increase the dehydrogenation rate - the amount of hydrogen released is increased by 0.7 wt.% when the dehydrogenation time is 5 minutes.
[0091] The cycle performance test results of MH-NSTi / Nb-O are as follows: Figure 7 As shown;
[0092] In the first cycle, the hydrogen storage capacity of MH-NSTi / Nb-O is 6.6wt.%,
[0093] After 200 cycles, the hydrogen storage capacity of MH-NSTi / Nb-O is 6.2 wt.%;
[0094] The capacity retention rate was 93.9% when the cycle number was 200.
[0095] The following conclusions can be drawn from a comprehensive comparison of Example 1 and Comparative Example 1:
[0096] 1. P123 has no substantial effect on the phase structure, and thus has no substantial effect on the complete hydrogen release capacity of the magnesium hydride composite hydrogen storage material, that is, the first cycle hydrogen release capacity;
[0097] 2. Adding P123 can realize self-assembly to form a three-dimensional structure, significantly increasing the specific surface area of the composite material by 69.4%, thereby significantly reducing the initial hydrogen desorption temperature of the magnesium hydride composite hydrogen storage material, and significantly improving the retention rate of hydrogen desorption and hydrogen storage capacity.
[0098] Comparative Example 2
[0099] A method for preparing a NSTi / Nb-O composite material based on a template agent PEI, wherein the steps not specifically described are the same as those in Example 1, except that: in step 1, the template agent is replaced by PEI instead of P123. The obtained composite material is abbreviated as NSTi / Nb-O-PI, and the obtained magnesium hydride composite hydrogen storage material is abbreviated as MH-NSTi / Nb-O-PI.
[0100] The TPD test results of MH-NSTi / Nb-O-PI are as follows: Figure 5 As shown, the initial dehydrogenation temperature of the MH-NSTi / Nb-O-PI composite hydrogen storage material is 207° C. Compared with the MH-NSTi / Nb-O obtained in Comparative Example 1, it can be seen that the introduction of PEI as a template agent actually increases the initial dehydrogenation temperature.
[0101] The hydrogen desorption test results of MH-3DNSTi / Nb-O-PI are as follows: Figure 6 As shown in the figure, when the hydrogen desorption time is 5 minutes, the amount of hydrogen released is 5.2 wt.%, and when the hydrogen desorption time is 25 minutes, the total amount of hydrogen released is 6.6 wt.%. Compared with the MH-NSTi / Nb-O obtained in Comparative Example 1, the introduction of PEI as a template has no substantial effect on the total amount of hydrogen released. However, it leads to a significant decrease in the hydrogen desorption rate - when the hydrogen desorption time is 5 minutes, the amount of hydrogen released is reduced by 0.5 wt.%.
[0102] Comparative Example 3
[0103] A method for preparing an NSTi / Nb-O composite material based on a template agent PDMS, wherein the steps not specifically described are the same as those in Example 1, except that in step 1, the template agent is replaced by PDMS instead of P123. The resulting composite material is referred to as NSTi / Nb-O-PS. Furthermore, the subsequently obtained magnesium hydride composite material is referred to as MH-NSTi / Nb-O-PS.
[0104] The TPD test results of MH-NSTi / Nb-O-PS are as follows: Figure 5 As shown, the initial dehydrogenation temperature of the MH-NSTi / Nb-O-PS composite hydrogen storage material is 199° C. Compared with the MH-NSTi / Nb-O obtained in Comparative Example 1, it can be seen that the introduction of PDMS as a template actually increases the initial dehydrogenation temperature.
[0105] The isothermal hydrogen desorption test results of MH-NSTi / Nb-O-PS are as follows: Figure 6 As shown in the figure, when the dehydrogenation time is 5 minutes, the amount of hydrogen released is 4.0 wt.%, and when the dehydrogenation time is 25 minutes, the total amount of hydrogen released is 6.6 wt.%. Compared with the MH-NSTi / Nb-O obtained in Comparative Example 1, the introduction of PDMS as a template has no substantial effect on the total amount of hydrogen released. However, it leads to a significant decrease in the dehydrogenation rate. When the dehydrogenation time is 5 minutes, the amount of hydrogen released is significantly reduced by 1.7 wt.%.
[0106] The following conclusions can be drawn from Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3:
[0107] 1. Adding conventional templates PEI and PDMS will increase the initial hydrogen desorption temperature of the composite hydrogen storage material;
[0108] 2. Although the addition of conventional templates PEI and PDMS has no substantial effect on the complete hydrogen desorption capacity of the composite hydrogen storage material, it will significantly reduce the hydrogen desorption rate.
[0109] The reasons for the above phenomenon are:
[0110] P123 is characterized by its composition of hydrophilic and hydrophobic groups. When used as a template, it guides the formation of uniform mesoporous and macroporous structures through the hydrophilic-hydrophobic balance, achieving the effect of regulating the pore structure and interfacial properties. Ultimately, it achieves the simultaneous increase of active site density without introducing chemical residues or changing the phase structure.
[0111] PEI is rich in amino groups, i.e., a strongly cationic polymer. When used as a template, it generates strong electrostatic interactions with negatively charged metal salts, which directly leads to rapid precipitation and localized uneven concentration, ultimately preventing the formation of an ordered structure.
[0112] PDMS has the characteristic of poor compatibility with aqueous precursors. When used as a template, it cannot form a stable self-assembly template, which hinders the uniform dispersion of the precursor. In addition, PDMS also has the characteristic of incomplete decomposition during high-temperature calcination, which directly leads to residual silicon oxide covering the active sites and reducing the reaction activity of the material.
[0113] In order to further demonstrate the role of the fluoride ion regulator in the technical solution, Comparative Example 4 is provided, which is a Ti / Nb-O composite material prepared using ammonium fluoride as a fluorine source.
[0114] Comparative Example 4
[0115] A method for preparing a Ti / Nb-O composite material based on ammonium fluoride as a fluorine source, wherein the steps not specifically described are the same as those in Example 1, except that: in step 1, ammonium fluorotitanate and boric acid, which are fluoride ion regulators, are not added. At the same time, titanium sulfate is added as a titanium source and ammonium fluoride is added as a fluoride ion regulator. The obtained Ti / Nb-O composite material is referred to as Ti / Nb-O-TS. Furthermore, the subsequently obtained magnesium hydride composite hydrogen storage material is referred to as MH-Ti / Nb-O-TS.
[0116] The TPD test results of MH-Ti / Nb-O-TS are as follows: Figure 5 As shown, the initial dehydrogenation temperature of MH-Ti / Nb-O-TS is 232° C. Compared with the MH-3DNSTi / Nb-O obtained in Example 1, it can be seen that the use of conventional fluoride ion regulator actually increases the initial dehydrogenation temperature.
[0117] The hydrogen desorption test results of MH-NSTi / Nb-O-TS are as follows: Figure 6 As shown, when the dehydrogenation time is 5 minutes, the amount of hydrogen released is 4.7 wt.%, and when the dehydrogenation time is 25 minutes, the total amount of hydrogen released is 6.6 wt.%. Compared with the MH-3DNSTi / Nb-O obtained in Example 1, it can be seen that although the use of ammonium fluorotitanate and boric acid as fluoride ion regulators has no substantial effect on the total amount of hydrogen released, they can significantly increase the hydrogen release rate - when the dehydrogenation time is 5 minutes, the amount of hydrogen released is significantly increased by 1.7 wt.%.
[0118] A comprehensive comparison of Example 1 and Comparative Example 4 leads to the following conclusion: While the use of ammonium fluorotitanate and boric acid as fluoride regulators has no substantial effect on the total amount of hydrogen released, it can significantly reduce the initial hydrogen release temperature and significantly increase the hydrogen release rate. This is because ammonium fluorotitanate, as a titanium source, simultaneously generates TiO2 and releases fluoride ions during hydrolysis, which, together with boric acid, regulates the fluoride ion concentration, establishes a dynamic equilibrium, and achieves precise control of the degree of anisotropy during crystal growth. Conversely, the use of ammonium fluoride as a fluoride source in combination with titanium sulfate, a conventional titanium source, results in localized fluoride ion supersaturation, leading to abnormal crystal growth.
Claims
1. A 3DNSTi / Nb-O composite material based on template P123, characterized by: Using niobium oxalate as the niobium source, ammonium fluorotitanate as the titanium source and fluoride ion regulator, boric acid as the fluoride ion regulator, and P123 as the template, first, a 3DNSTi / Nb-O composite material based on the template P123 was synthesized by a hydrothermal method. Then, P123 was removed by heat treatment in air to obtain 3DNSTi / Nb-O.
2. The 3DNSTi / Nb-O composite material according to claim 1, wherein: The 3DNSTi / Nb-O is anatase TiO2, and Nb element is doped into the TiO2 lattice; the 3DNSTi / Nb-O has oxygen vacancies.
3. The 3DNSTi / Nb-O composite material according to claim 1, wherein: The microstructure of the 3DNSTi / Nb-O is a three-dimensional structure composed of nanosheets; the specific surface area is 25-35m 2 / g.
4. A method for preparing a 3DNSTi / Nb-O composite material based on a template P123, characterized in that The following steps are involved: First, a niobium source, a fluoride ion regulator, a titanium source and a template are prepared in a certain proportion to prepare raw materials. Then, under certain conditions, the niobium source, the fluoride ion regulator, the titanium source and the template are placed in deionized water and stirred and dissolved to obtain a reaction solution. Thereafter, the reaction solution is subjected to a hydrothermal reaction. After the reaction is completed, the obtained precipitate is filtered, washed and dried to obtain a Nb-doped TiO2 nanosheet self-assembled 3D structure composite material. Finally, under certain conditions, the Nb-doped TiO2 nanosheet self-assembled 3D structure composite material is heat-treated to remove the template, and finally a template-based 3DNSTi / Nb-O composite material with a self-assembled 3D structure is obtained, which is referred to as 3DNSTi / Nb-O.
5. The preparation method according to claim 4, wherein: The niobium source is niobium oxalate; the titanium source is ammonium fluorotitanate; the fluoride ion regulator is boric acid, and ammonium fluorotitanate is also a fluoride ion regulator; and the template is P123.
6. The preparation method according to claim 4, wherein: The mass ratio of niobium oxalate, boric acid and ammonium fluorotitanate is (0.025-0.3):(0.25-2):1, and the mass ratio of template to titanium source is 1:(1-4); The stirring and dissolving conditions are as follows: the stirring and dissolving temperature is 25-60°C and the stirring and dissolving time is 10-60 minutes; The reaction temperature is 110-200°C and the reaction time is 4-10h; The drying conditions are as follows: drying temperature is 60-80°C and drying time is 6-12h; The heat treatment temperature is 500-950° C., the heating rate is 2-5° C. / min, and the heat treatment time is 1-8 hours.
7. A method for preparing a magnesium hydride composite hydrogen storage material based on 3DNSTi / Nb-O, characterized in that The following steps are involved: Under certain conditions, MgH2 and 3DNSTi / Nb-O are ball-milled to prepare a magnesium hydride composite hydrogen storage material based on 3DNSTi / Nb-O, referred to as MH-3DNSTi / Nb-O.
8. The preparation method according to claim 7, wherein: The ball milling conditions are as follows: the ball milling hydrogen pressure is 2-10 bar, the ball-to-powder ratio is (20-40):1, and the ball milling speed is 200-500 rpm.
9. The preparation method according to claim 7, wherein: The initial dehydrogenation temperature of the obtained MH-3DNSTi / Nb-O is 185-230°C; under the condition of a dehydrogenation temperature of 300°C and a dehydrogenation time of 5 minutes, the dehydrogenation amount is 6.0-6.5wt.%.
10. The preparation method according to claim 7, wherein: The obtained MH-3DNSTi / Nb-O has no significant hydrogen storage capacity when the number of hydrogen absorption and desorption is 1000-1500 times, and the hydrogen desorption capacity is maintained at 6.9-7.1wt.%; the complete hydrogen desorption time is less than 15 minutes.